Metacognition & learning process: Using think-aloud protocol (TAP) to understand students and their teacher’s reflection processes during a problem-solving situation - O. Bouiri; S. Lotfi; M. Talbi (Образование и наука)
Introduction. Today, the act of teaching has become increasingly intricate. Multiple fields of science now aid in comprehending this complexity, enabling instructors to support learners through-out their educational journey.Aim. The main aim of this study is to determine cognitive and metacognitive thinking process of students and their teachers during a problem-solving situation.Research methodology and methods. The authors used think-aloud protocol (TAP) in which students (12 participants at the same level) were asked to verbalise their thoughts during a learning activity (math exercise and written production). Similarly, during a pedagogical intervention, nine participants with varying levels of professional experience were required to articulate their professional practices as educators. It should be noted that our approach is purely qualitative following Ericsson and Simon’s approach, from data collection step to coding system and processing of these data.Results and scientific novelty. The results showed that half of the students solved well what was asked in the problem-solving situation, contrary to the other participants who found particular difficulties in each type of situation proposed (in math and in written production). For the teachers, their verbalisations tend towards three aspects with a degree of dominance for each teacher. The authors consider hat their research is a first step towards a new approach of evaluation of the teaching-learning act that includes both the teacher and the learners simultaneously.Practical significance. The results obtained can be used by pedagogical practitioners to better understand how their learners think on the one hand and develop their professional practices on the other.